Economic evaluation of ombitasvir/paritaprevir/ritonavir and dasabuvir for the treatment of chronic genotype 1 hepatitis c virus infection. (2nd October 2016) - Johnson, Scott J.; Parisé, Hélène; Virabhak, Suchin; Filipovic, Ivana; Samp, Jennifer C.; Misurski, Derek
Abstract: Objectives: To estimate clinical outcomes and cost-effectiveness of ombitasvir/paritaprevir/ritonavir and dasabuvir ± ribavirin (OMB/PTV/r + DSV ± RBV) compared with treatment regimens including pegylated interferon (PegIFN) for patients with chronic genotype 1 hepatitis C virus (HCV) infection. Methods: An Excel spreadsheet Markov model tracking progression through stages of liver disease was developed. Costs and patient utilities for liver disease stages were taken from published studies. Rates of disease progression were based on studies of untreated HCV infection and long-term follow-up of those achieving sustained virologic response (SVR) after drug treatment. Impact of OMB/PTV/r + DSV ± RBV and other drug regimens on progression was estimated through SVR rates from clinical trials. Analyses were performed for treatment-naive and treatment-experienced patients. Impact of alternative scenarios and input parameter uncertainty on the results were tested. Results: For genotype 1 treatment-naive HCV patients, for OMB/PTV/r + DSV ± RBV, PegIFN + ribavirin (PegIFN/RBV), sofosbuvir + PegIFN/RBV, telaprevir + PegIFN/RBV, boceprevir + PegIFN/RBV, lifetime risk of decompensated liver disease was 5.6%, 18.9%, 7.4%, 11.7%, and 14.9%; hepatocellular carcinoma was 5.4%, 9.2%, 5.7%, 7.0%, and 7.4%; and death from liver disease was 8.7%, 22.2%, 10.4%, 14.8%, and 17.6%, respectively. Estimates of the cost-effectiveness of OMB/PTV/r + DSV ± RBV for treatment-naive and treatment-experienced patients indicated that it dominated all other regimens except PegIFN/RBV. Compared with PegIFN/RBV, the incremental cost-effectiveness ratios were £13, 864 and £10, 258 per quality-adjusted life-year (QALY) for treatment-naive and treatment-experienced patients, respectively. The results were similar for alternative scenarios and uncertainty analyses. Limitations: A mixed-treatment comparison for SVR rates for the different treatment regimens was not feasible, because many regimens did not have comparator arms; instead SVR rates were based on those from recent trials. Conclusions: OMB/PTV/r + DSV ± RBV is a cost-effective oral treatment regimen for chronic genotype 1 HCV infection compared with standard treatment regimens and is estimated to reduce the lifetime risks of advanced liver disease.